2017
DOI: 10.1016/j.joms.2016.12.024
|View full text |Cite
|
Sign up to set email alerts
|

Routine Postoperative Imaging Is Not Indicated in the Management of Mandibular Fractures

Abstract: Routine postoperative CT scans were found to have no significant effect on outcomes and complications, and a clinician's individual practice was the most significant factor for whether a patient received a routine postoperative CT scan. Future work should aim at providing well-defined indications for postoperative imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…77 In addition, the findings by Jain et al found that the routine use of postoperative radiographs had no significant effect in management of maxillofacial fractures. 78 This idea has also been supported by the work of Courtemanche et al 78 While these authors have demonstrated that postoperative imaging does not change management for patients with mandibular fractures following operative treatment, there remains a role for post-operative imaging to assess results and for educational purposes. In this context, surgeons should consider the balance between obtaining unnecessary imaging with the practical educational benefit for surgeon and trainee that comes from critical assessment of results using radiography.…”
Section: Three-dimensional Printingmentioning
confidence: 96%
“…77 In addition, the findings by Jain et al found that the routine use of postoperative radiographs had no significant effect in management of maxillofacial fractures. 78 This idea has also been supported by the work of Courtemanche et al 78 While these authors have demonstrated that postoperative imaging does not change management for patients with mandibular fractures following operative treatment, there remains a role for post-operative imaging to assess results and for educational purposes. In this context, surgeons should consider the balance between obtaining unnecessary imaging with the practical educational benefit for surgeon and trainee that comes from critical assessment of results using radiography.…”
Section: Three-dimensional Printingmentioning
confidence: 96%